Controlling Temperature and Water Loss to Maintain Ascorbic Acid Levels in Strawberries During Postharvest Handling - Nunes, M. C. N. (2011)
Chandler’, ‘Oso Grande’ and ‘Sweet Charlie’ strawberries were stored for 8 days at 1 or 10°C, or 4 days at 20°C, either unwrapped or wrapped in PVC film to retard were conducted during the 1 water loss. Total ascorbic acid (AA) content was expressed on a dry weight basis to correct for water loss differences between treatments. Loss of AA was low and did not differ between wrapped treatments at 1 and 10°C, but was much greater at 20°C. Wrapping reduced AA loss by 5-fold at 1 and 10°C and by 2-fold at 20°C. The effect was not due to modification of O2 and CO2 levels in wrapped treatments, which was minimal. The results indicate that water loss had a greater effect on AA levels than temperature. Combining wrapping with storage at 1 or 10°C reduced AA loss by 7.5-fold compared to unwrapped strawberries stored at 20°C.